1987
DOI: 10.1086/337641
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Morphological Responses to Irradiance in Three Forest Understory Species of the C4Grass Genus Muhlenbergia

Abstract: Three species of the C 4 grass genus Muhlenbergia-M. frondosa, M. sobolifera, and M. schreberiwere collected from forest understory sites in northeastern Kansas and grown in a growth chamber at 1,500, 150, and 15-25 fjimol m~2 s -1 photosynthetic photon flux density (PPFD). Leaf, stem, root, and total biomasses and several morphological and anatomical characteristics were measured after 35-38 days. Results were compared with similar measurements for M. cuspidata collected from exposed prairie sites. Although a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 25 publications
(28 reference statements)
1
15
1
Order By: Relevance
“…Statistical difference was inferred when P < .05. Fresh leaf sections were prepared to determine A mes /A ratios (SMITH and MARTIN 1987). Measurements of A mes /A ratios for M. frondosa, M. sobolifera, andM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical difference was inferred when P < .05. Fresh leaf sections were prepared to determine A mes /A ratios (SMITH and MARTIN 1987). Measurements of A mes /A ratios for M. frondosa, M. sobolifera, andM.…”
Section: Methodsmentioning
confidence: 99%
“…The discrepancy in A between plants of M. schreberi from the medium PPFD regime and those from the high PPFD treatment is difficult to interpret in view of the optimal growth of this species at the highest PPFD level (SMITH and MARTIN 1987).…”
Section: Photosynthetic Gas Exchangementioning
confidence: 97%
“…to the understory resulted in a significantly lower biomass and leaf area compared to the open. In addition, Smith and Martin (1987b) found that the shade intolerant Muhlenbergia cuspidata died after 30 d at low light intensities in Kansas, USA. Similar findings were reported by Winter et al (1982) for the shade intolerant C 4 Digitaria sanguinalis.…”
mentioning
confidence: 99%
“…Thus, thicker sun-acclimated leaves may have higher photosynthetic rates that saturate at higher photosynthetic photon flux density (PPFD) than do shade-acclimated leaves Smith and Martin, 1987). Leaf thickening is often accompanied by an increase in cell size and number of both spongy mesophyll and palisade cells tliat results in increased mesophyll cell surface area and volume .…”
Section: General Introductionmentioning
confidence: 99%
“…Thus, sun-acclimated leaves may have higher photosynthetic rates that saturate at higher photosynthetic photon flux density (PPFD) than do shade-acclimated leaves Smith and Martin, 1987). In some species leaf mesophyll cell surface area per unit leaf area (Ames/A) has been positively correlated with the leaf photosynthetic capacity and water use efOciency (WUE), i.e., the amount of carbon fixed per unit of water transpired .…”
Section: Introductionmentioning
confidence: 99%